Why can spontaneous intracranial hypotension cause behavioral changes? A case report and multimodality neuroimaging comparison with frontotemporal dementia. (October 2022) - Carbone, Chiara; Bardi, Elisa; Corni, Maria Giulia; Balboni, Erica; Filippini, Nicola; Fiondella, Luigi; Salemme, Simone; Vinceti, Giulia; Molinari, Maria Angela; Tondelli, Manuela; Chiari, Annalisa; Zamboni, Giovanna
Abstract: Frontotemporal Brain Sagging Syndrome (FBSS) is a rare condition characterized by the presence of spontaneous intracranial hypotension associated with behavioural disturbances mimicking the behavioural variant of Frontotemporal dementia (bvFTD). It has been suggested that behavioural symptoms are caused by damage to the connectivity of the frontal lobes due to the brain sagging. However, no studies have directly explored brain connectivity in patients with FBSS. Here, we report a new case of FBSS with persistent behavioural disturbances, whom we compared to 20 patients with bvFTD and to 13 cognitively healthy controls using Magnetic Resonance Imaging (MRI). We explored differences related to grey matter (GM) volume with voxel-based morphometry, functional connectivity with seed-based analysis, and white matter (WM) microstructural integrity with tract-based spatial statistics. We found that the FBSS patient, like the controls, had greater GM volume relative to the bvFTD patients. Moreover, the FBSS patient had greater functional connectivity from a left inferior frontal gyrus seed than both the bvFTD patients and healthy controls groups in dorsolateral frontal areas. Like the bvFTD group the FBSS patient had decreased WM integrity relative to the controls, especially in the posterior part of the corpus callosum, and the magnitude of these abnormalities correlated with measures of apathy across the FBSS and bvFTD patients. Our results suggest that behavioural changes associated with SIH are mainly due to altered WM connectivity.